Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Di Astagina Resort Villa And Spa Legian Bali - Agnesia Margareth Aruan; I Made Bayu Wisnawa (Universitas Triatma Mulya, 2025)
The purpose of this research was to determine the effect of work motivation on working performance in Astagina Resort vila and Spa. The methods used to collect data were questionnaire, interview, and documentation. The result shows that work motivation (x) has positive and significant effect toward employee performance in Astagina Resort and Villa and Spa. Besides that, the result also shows that the amount of determination was 46,8% which means that 46,8 % of Astagina Employee of Astagina Resort Villa and Spa were affected by work motivation (X) and the rest (53,2%) was affected by another variable which is not used in this research. It is suggested that Astagina Resort Villa and Spa Management can increase motivation by giving bonus, reward or other reinforcement which can trigger the increase of working performance. If it is applied, indirectly, it will increase working performance and visitor who stay in Astagina Resort and Spa will also increase. The management is hoped to provide training to staff so that employee can fisihh their job effectively.